2009
DOI: 10.1111/j.1742-1241.2009.02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between painful physical symptoms and clinical outcomes in East Asian patients with major depressive disorder: a 3-month prospective observational study

Abstract: As the presence of PPS is associated with poorer outcomes in East Asian MDD patients, clinical management should aim to address both the mental and PPS associated with MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…In the present study, 61 of 100 MDD subjects reported having PPS, which is consistent with results from other studies (Ang et al, 2009;Agüera-Ortiz et al, 2011;Shimodera et al, 2012;Novick et al, 2013a;Kishi et al, 2015). In this study, no significant difference was observed in age and gender between the PPSþ and PPS-groups.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, 61 of 100 MDD subjects reported having PPS, which is consistent with results from other studies (Ang et al, 2009;Agüera-Ortiz et al, 2011;Shimodera et al, 2012;Novick et al, 2013a;Kishi et al, 2015). In this study, no significant difference was observed in age and gender between the PPSþ and PPS-groups.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the MDD remission rate in this study was high, at 84%, despite the presence or absence of PPS (PPS þ ¼85.2%, PPS-¼82.1%), and no significant differences were found between the groups. Patients with PPS have been reported to have more severe depression Novick et al, 2013bNovick et al, , 2015, and PPS is associated with a reduced quality of life (Novick et al, 2013a), worse clinical outcome (Ang et al, 2009), and limited improvement (Husain et al, 2007). The differences observed between this study and previous reports regarding MDD severity and remission rate in the PPSþ and PPS-groups were likely due to the fact that our MDD patients had melancholic features.…”
Section: Discussionmentioning
confidence: 56%
“…16,[33][34][35][36] Table 4 shows that participants with higher levels of pain experienced greater severity of adverse events during the treatment period. The mean (SD) of baseline UKU score was 6.3 (6.8).…”
Section: Discussionmentioning
confidence: 96%
“…The American Psychiatric Association guideline for the treatment of patients with MDD 44 emphasizes the importance of adding functional measures to adequately capture the full impact of depression and its treatment. To our knowledge, most of the previous studies used symptom severity as outcome measure, 16,[33][34][35][36] whereas only a few studies measured functional outcome. 45 In addition, using continuous variables (ie, HAMD-17 score and MWSAS score) as outcome measures is more precise than using dichotomized outcomes (eg, response/nonresponse or remission/nonremission).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation